1999
DOI: 10.1901/jaba.1999.32-479
|View full text |Cite
|
Sign up to set email alerts
|

Relative Versus Absolute Reinforcement Effects: Implications for Preference Assessments

Abstract: We compared results obtained in two previous studies on reinforcer identification (Fisher et al., 1992; Pace, Ivancic, Edwards, Iwata, & Page, 1985) by combining methodologies from both studies. Eight individuals with mental retardation participated. During Phase 1, two preference assessments were conducted, one in which stimuli were presented singly (SS method) and one in which stimuli were presented in pairs (PS method). Based on these results, two types of stimuli were identified for each participant: High-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
127
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(145 citation statements)
references
References 12 publications
17
127
1
Order By: Relevance
“…Although our data suggest that caregivers may not be using the most preferred item when they repeatedly and exclusively deliver the highest ranked item identified during a pretreatment assessment, it is unclear that identifying and using temporarily more preferred items on a regular basis would produce clinically meaningful improvements under typical training conditions. For example, Roscoe, Iwata, and Kahng (1999) demonstrated that, although a greater proportion of responses were allocated towards higher preference items than lower preference items during concurrent-operant tasks, the higher preference item rarely produced higher absolute response rates during single-operant tasks. Similar results may apply to items identified during pretreatment assessments versus daily preference assessments, in that top-ranked items may produce indistinguishable absolute response rates regardless of when they were identified as most preferred.…”
Section: Resultsmentioning
confidence: 99%
“…Although our data suggest that caregivers may not be using the most preferred item when they repeatedly and exclusively deliver the highest ranked item identified during a pretreatment assessment, it is unclear that identifying and using temporarily more preferred items on a regular basis would produce clinically meaningful improvements under typical training conditions. For example, Roscoe, Iwata, and Kahng (1999) demonstrated that, although a greater proportion of responses were allocated towards higher preference items than lower preference items during concurrent-operant tasks, the higher preference item rarely produced higher absolute response rates during single-operant tasks. Similar results may apply to items identified during pretreatment assessments versus daily preference assessments, in that top-ranked items may produce indistinguishable absolute response rates regardless of when they were identified as most preferred.…”
Section: Resultsmentioning
confidence: 99%
“…We examined that possibility in the present study by teaching individuals to tact objects for which preference had been established previously through formal assessment. Results of a number of studies on the assessment of preference have shown that, when a preferred and a nonpreferred item are available in a free-operant concurrent arrangement, participants allocate responses toward the preferred item (Fisher et al, 1992;Roscoe, Iwata, & Kahng, 1999). Thus, we taught participants to tact preferred and nonpreferred items and predicted that, if mands emerged, they would favor the preferred items.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…First, the two general patterns of responding (preference for HQ during the HQ vs. VLQ condition; switching during the HQ vs. VSLQ condition) were not observed for every participant (see Josh and Matt), and it is likely that these patterns were influenced by either the specific stimuli or the number of stimuli included in the initial preference assessments. In other words, although it seemed reasonable to define preference (HQ, SLQ, LQ) based on rankings, a given ranking may not be predictive of a reinforcement effect (Roscoe, Iwata, & Kahng, 1999). Depending on which and how many stimuli are included in a preference assessment, it is possible that few stimuli, all stimuli, or all stimuli above a given rank would function as reinforcers.…”
Section: Experimental Designmentioning
confidence: 99%
“…A singlestimulus preference assessment (Pace et al, 1985) was conducted to identify nonpreferred (NP) stimuli. The rationale for using this assessment was that stimuli not selected in a paired-stimulus format may nevertheless function adequately as reinforcers (Roscoe et al, 1999); as a result, we felt that nonapproach to a stimulus presented singly would yield more valid information about lack of preference. Each participant was allowed to sample each item prior to the start of the assessment.…”
Section: Preference Assessmentmentioning
confidence: 99%